KINERJA AGROINDUSTRI KERIPIK PISANG DI KECAMATAN TANJUNG RAJA KABUPATEN LAMPUNG UTARA - Deta Delima; Yaktiworo Indriani; Adia Nugraha (Lampung University, 2023)
This research aims to analyze the procurement of raw materials, processing, profits and marketing of banana chips in Tanjung Raja District, North Lampung Regency. The research method used is a case study by determining the research location purposively at the Siti, Farida and Giyarti Agroindustry. Data collection was obtained through observation and interviews using questionnaires collected from May to June 2022 at the Siti, Farida and Giyarti Banana Chips Agroindustry. Data analysis was carried out using qualitative descriptive analysis (processing analysis and marketing mix analysis) and quantitative descriptive analysis (EOQ, FIFO and profit analysis). The research results showed that the optimal amount of banana inventory based on the EO method at the Siti, Farida and Giyarti Agroindustry were 63.56 kg, 50.67 kg, 44.33 kg with an ordering frequency of 95 times. The final inventory value of bananas based on the FIFO method at the three Agro-industries in 2021 were IDR 8,853,000.00, IDR 2,298,000.00 and IDR 2,940,000.00, respectively. The processing processes at the three agro-industries include peeling, slicing, frying, draining, cooling, adding flavoring powder and packaging. The marketing mix at the three Agro-industries applies product, price, place, promotion, human resources, process and physical evidence. Profit per production at Siti, Farida and Giyarti Agroindustry respectively amounted to IDR 8,942,657.75; Rp. 2,958,631.94; and IDR 1,842,164.58 with a selling price per 200 grams of IDR 12,000 at Siti Agroindustry and IDR 10,000 at Farida and Giyarti Agroindustry. Key words: EOQ, FIFO, marketing mix, processing and profit